Hermite-Hadamard Type Fractional Integral Inequalities for Preinvex Functions (Communications in Mathematical Research, 2019)
In this article, we extend some estimates of the right-hand side of theHermite-Hadamard type inequality for preinvex functions with fractional integral.The notion of logarithmically s-Godunova-Levin-preinvex function in second sense isintroduced and then a new Hermite-Hadamard inequality is derived for the class oflogarithmically s-Godunova-Levin-preinvex function.
Keywords: Hermite-Hadamard's integral inequality; Riemann-Liouville fractional integral; Hölder's integral inequality